1984
DOI: 10.1007/bf03015401
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane-induced hypotension does not cause impairment in pulmonary gas exchange

Abstract: Induced hypotension during anaesthesia can result in deterioration in gas exchange with increases in intrapulmonary shunting and physiological deadspace. Cardiovascular stability has been previously demonstrated with isoflurane-induced hypotension but the effects on gas exchange have not been carefully studied. We have examined the shunt fraction (QS/QT) and physiological dead space to tidal volume ratio (VD/VT) before, during and following deliberate hypotension in twelve patients. Group I (n = 6) received an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 17 publications
0
4
1
1
Order By: Relevance
“…These are arguments for the good tolerance of the cardiovascular system for isoflurane, with respect to cardiac output and tissue perfusion. Controlled depression of haemodynamics and with it reduced VO~ was accomplished with isoflurane in contrast to SNP which led to unnecessary increases in CI and ~'O2-Furthermore, there was a lack of variation of pulmonary arterial pressures and pulmonary vascular resistance, as shown by Klide 24 and Moffit et al 2~ Finally, the intrapulmonary shunt fraction remained unchanged, as reported by Nicholas and Lam,26 in contrast to what is seen with SNP. s'2~…”
Section: Discussioncontrasting
confidence: 36%
“…These are arguments for the good tolerance of the cardiovascular system for isoflurane, with respect to cardiac output and tissue perfusion. Controlled depression of haemodynamics and with it reduced VO~ was accomplished with isoflurane in contrast to SNP which led to unnecessary increases in CI and ~'O2-Furthermore, there was a lack of variation of pulmonary arterial pressures and pulmonary vascular resistance, as shown by Klide 24 and Moffit et al 2~ Finally, the intrapulmonary shunt fraction remained unchanged, as reported by Nicholas and Lam,26 in contrast to what is seen with SNP. s'2~…”
Section: Discussioncontrasting
confidence: 36%
“…Two articles suggested that minimal pulmonary derangement 117 and mild pancreatic stress 132 were induced by hypotension. None of them showed a significant adverse outcome due to induced hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen articles demonstrated other systemic effects of hypotensive anaesthesia: 3 randomized clinical trials 63,117,132 , 2 controlled clinical trials 44,106 , 7 prospective case series 7,25,58,100,104,126,188 , 1 retrospective case series 182 and 1 case report 30 . The 3 randomized clinical trials were selected for critical appraisal (Table 8).…”
Section: Other Systemic Effects Of Hypotensive Anaesthesiamentioning
confidence: 97%
“…However, when hypotension is induced with isoflurane, gas exchange is not affected significantly, suggesting that nitroprusside itself, may have an effect on pulmonary gas exchange rather than hypotension per se. 36 Because hypotension in the ponies in this present study was induced with isoflurane, it seems unlikely that hypotension alone was responsible for the lack of response to PiNO; more, it was the combination of MV and hypotension.…”
Section: Discussionmentioning
confidence: 77%